2019
DOI: 10.1108/ijse-03-2018-0148
|View full text |Cite
|
Sign up to set email alerts
|

Trends and causes of socioeconomic inequalities in maternal healthcare in Ghana, 2003–2014

Abstract: Purpose The purpose of this paper is to assess the trends of socioeconomic-related inequalities in maternal healthcare utilization in Ghana between 2003 and 2014 and examine the causes of inequalities in maternal healthcare utilization in Ghana. Design/methodology/approach Data are drawn from three rounds of the Ghana Demographic and Health Survey collected in 2003, 2008 and 2014, respectively. The authors employ two alternative measures of socioeconomic inequalities in health – the Wagstaff and Erreygers in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 49 publications
(141 reference statements)
6
21
1
Order By: Relevance
“…Data for this study were collected from the Ghana Demographic and Health Survey (GDHS) conducted in 2014[25]. Specifically, the women and child files were used for the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data for this study were collected from the Ghana Demographic and Health Survey (GDHS) conducted in 2014[25]. Specifically, the women and child files were used for the study.…”
Section: Methodsmentioning
confidence: 99%
“…Various supply and demand side strategies have been proposed and implemented to promote MHS utilisation[9, 21] including home visiting, community education programmes and financial approaches e.g. maternal health insurance schemes in several Asian and African countries [2224] including the National Health Insurance Scheme of Ghana[25, 26]. However, the impact of insurance programmes on promoting MHS has not been deeply studied to understand to what extent the increasing utilisation resulted from insurance policies, which constraints reaching conclusive findings.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al, 2019;R. Zhang et al, 2018) by numerous socioeconomic, cultural, demographic and community-level factors (Fenny et al, 2019;Rajesh Kumar Rai et al, 2012) which make difficulties for the poor and vulnerable groups to get full access and ideal use of maternal healthcare (Novignon et al, 2019). However, have been found that significant inequalities exist especially in Asian and African context and the severity reach its pick in Afghanistan, Somalia, and South Sudan.…”
Section: Resultsmentioning
confidence: 99%
“…There are a number of studies all around the globe that have already looked up the measure to find out the role of income inequalities in the utilization of maternal health care. In this context, Ambel et al 2017, Fenny et al (2019) and Novignon et al (2019) in their research in Ghana, with the same data set, found that the pro-rich characteristics of the household significantly ensure the utilization of ANC services than their poorer counterparts. The same situation exists in Bangladesh, a South-Asian country, the evidence of which is explored in the study of Pulok et al 2018, Rana et al (2019), according to these studies, women from higher income strata are more likely to get access in maternal health-related services both from public and private service providers in comparison with their poor counterparts.…”
Section: Incomementioning
confidence: 94%
“…Studies have identified individual and geographical factors that influence the use of SBA services. Some of the important individual-level determinants are education, wealth, age, health insurance, parity and quality of antenatal care received [9][10][11][12]. Women's ability to afford maternal health services, understand risks of childbirth and availability of comprehensive maternal health services are important in choosing where to give birth.…”
Section: Introductionmentioning
confidence: 99%